DETERMINATION OF THE COMPOSITION AND QUANTITY OF MACRO- AND MICROELEMENTS OF THE PLANT GERANIUM COLLINUM (Scientific journal of the Fergana State University, 2023)
The elemental composition of samples of leaves and stems of Geranium collinum was studied in detail for the first time using inductively coupled plasma mass spectrometry on an ICP-MS AT 7500 instrument. 43 elements were quantitatively determined in the organs of Geranium collinum. It has been noted that 43 elements are present in the leaves and 42 elements in the stems of the Geranium collinum plant. A natural tendency for the amount of the element to decrease with increasing mass is shown.